Interweaving Identities: Cultural Synthesis and Societal Dynamics in Zadie Smith’s Swing Time - Gheytasi, Sajjad (Linguæ & - Journal of Modern Languages and Cultures, 2024)
Zadie Smith's Swing Time masterfully engages with global encounters through intricate literary techniques, transcending biases. The novel's interplay of form and content reveals interactive processes inherent in approaching texts as social events. This analytical lens unveils narrative layers and underlying societal currents that shape character dynamics and interactions. The novel's narrative strategy serves as a canvas for weaving diverse cultural threads, challenging conventional narratives. Swing Time deftly interweaves elements from a wide spectrum of identities, skillfully bridging the disjointed segments of the protagonist's multifaceted journey. This narrative technique effectively fuses cultural and historical symbols, enabling a synthesis that redefines historical understanding. In navigating global influence, the novel offers a nuanced interpretation of hegemony, intertwining historical epochs and events into a comprehensive framework. In the context of globalization, Smith's intertextual references weave dance history into the narrative, transcending boundaries of race and time, fostering empathy and unity. Swing Time challenges norms through multifaceted aesthetic values, prompting introspection and advocating for an equitable society. The present study analyzes the novel's exploration of identity, empathy, and the transformative power of art in shaping a more inclusive world. Through its intricate narrative, Swing Time effectively crafts a rich tapestry of interwoven identities, thereby deepening our understanding of the text and the intricate societal currents it engages with. The novel's discourse transcends mere entertainment, provoking readers to reflect on the interconnectedness of narratives across time and space.